Hydrogeology of the lower sector of Basento and Cavone river basins (southern Italy) - Silvio Coda; Pasquale Allocca; Domenico Calcaterra; Nicola Castello; Delia Cusano; Pantaleone De Vita; Daniele Lepore; Paola Petrone; Giacomo Prosser; Vincenzo Allocca (Journal of Maps)
Hydrogeology of the lower sector of the Basento and Cavone river basins (southern Italy), has been little studied so far, although this area plays a strategic role being an agricultural area, for the production of wheat and organic olive oil, and represents a historical economic pole, with the presence of an industrial area and several extraction sites of natural gas. In this paper, starting from official Italian geological maps, a hydrogeological conceptual model and geodatabase were developed through hydrogeological characterization of lithological formations, analysis of topographic cartography and satellite images, as well as an extensive hydrogeological survey. The results are represented by a hydrogeological map at the 1:50,000 scale, hydrostratigraphic cross-sections, groundwater flow schemes, and a groundwater database. These are valuable tools for knowledge and may be used as a reference for future hydrogeological studies, as well as planning and decision-making in groundwater management.